Do Leadership and Effective Internal Communication Strategies Really Matters? Insights from MNCs in the Malaysian Hospitality Industry - Amin Chowdhury, Iftekhar; Mohd Suki, Norazah; Rizal Abd, Mohd. (International Journal of Psychosocial Rehabilitation, 2019)
Studies on communication within MNCs and the effect on the global marketplace began as early as the 1970s. Leadership competencies have a profound impact on the type of communication strategies deployed within an organization. The purpose of this qualitative phenomenological study is to explore effective internal communication strategies used by leaders of MNCs in the hospitality industry in Malaysia. This conceptual study depicts the effect of leadership style on communication that occurs between leaders and subordinates via the leader-manager exchange (LMX) and the effect on the quality of communication. The aim of this research is to examine the relationship between the LMX and leadership strategy and the relevant linkage to communication within the multinational hospitality organizations in Malaysia. The research design that has been selected for this study is the interview of purposefully selected hospitality industry professionals in a leadership role. During the interview process, the study will use open-ended questions to allow participants to control responses and respond to follow-up questions. The interview sessions will be one-on-one closed sessions with industry leaders. The goal is to achieve a minimum sample size of 10 participants for the study. Research for this study will take place in a neutral setting away from daily business operations with the leaders from MNCs in the Malaysian hospitality industry. The qualitative software tool, Nvivo 11, will be the primary source for collecting and analyzing the data. It is expected that the participants will express their views that effective communication strategies between leaders and subordinates in the LMX influence productivity either positively or negatively